2013
DOI: 10.3390/geosciences3030354
|View full text |Cite
|
Sign up to set email alerts
|

Continental Growth and Recycling in Convergent Orogens with Large Turbidite Fans on Oceanic Crust

Abstract: Convergent plate margins where large turbidite fans with slivers of oceanic basement are accreted to continents represent important sites of continental crustal growth and recycling. Crust accreted in these settings is dominated by an upper layer of recycled crustal and arc detritus (turbidites) underlain by a layer of tectonically imbricated upper oceanic crust and/or thinned continental crust. When oceanic crust is converted to lower continental crust it represents a juvenile addition to the continental grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 135 publications
0
14
0
Order By: Relevance
“…2.00 and 1.95 Ga (Yin et al, 2011;Dan et al, 2012). As previously noted, the requirements for such rapid sedimentary recycling are only met in a few distinctive tectonic settings that involve processes such as lithospheric delamination, back-arc basin opening, mantle plume ascent or continental rifting Kemp et al, 2007;Zheng et al, 2008;Collins and Richards, 2008;Foster and Goscombe, 2013). A common feature of these tectonic settings is the presence of asthenosphere upwelling, consistent with the generation of high-temperature Stype granites (Sylvester, 1998).…”
Section: Source Components For S-type Granitesmentioning
confidence: 85%
See 1 more Smart Citation
“…2.00 and 1.95 Ga (Yin et al, 2011;Dan et al, 2012). As previously noted, the requirements for such rapid sedimentary recycling are only met in a few distinctive tectonic settings that involve processes such as lithospheric delamination, back-arc basin opening, mantle plume ascent or continental rifting Kemp et al, 2007;Zheng et al, 2008;Collins and Richards, 2008;Foster and Goscombe, 2013). A common feature of these tectonic settings is the presence of asthenosphere upwelling, consistent with the generation of high-temperature Stype granites (Sylvester, 1998).…”
Section: Source Components For S-type Granitesmentioning
confidence: 85%
“…Several mechanisms have been proposed to explain the rapid formation of S-type granites. For subduction systems or accretionary orogens, the rapid formation of S-type granites and related rocks has been accounted for by models of back-arc basin opening (Cenozoic Hidaka metamorphic belt, Japan; Kemp et al, 2007) and lithospheric delamination (Ordovician Lachlan Fold Belt, Australia; Foster and Goscombe, 2013) or by models that combine both features (Collins and Richards, 2008). The rapid formation of Stype granites in collisional orogenic belts, however, has commonly been attributed to mantle plumes (Jiangnan Orogen, South China Block, Li et al, 2003) or continental rifting (Jiangnan Orogen, Zheng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the Paleozoic and Mesozoic metasedimentary successions of eastern Australia and Zealandia (hereinafter basement rocks) are either submerged or concealed under younger sedimentary cover. Basement rocks of these regions typically contain a large component of multi-cycled Gondwanan detritus (Fergusson & Henderson, 2015;Fergusson, Henderson, & Offler, 2017;Foster & Goscombe, 2013;Glen, 2013;Glen, Belousova, & Griffin, 2016). Detrital zircon studies in eastern Australia and the southwestern Pacific region have shown that both sedimentary (Shaanan & Rosenbaum, 2018;Sircombe, 1999) and magmatic (Buys, Spandler, Holm, & Richards, 2014;Tapster, Roberts, Petterson, Saunders, & Naden, 2014) recycling took place.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, this crust could also comprise felsic upper crust over a Grenville-age, or even older (see Schilling et al, 2017), mafic lower crust, as we postulated for the crust farther north. We note that such heterogeneous crust was formed ubiquitously in collisional settings around the Gondwana perimeter (Foster and Goscombe, 2013), including, apparently, in Patagonia.…”
Section: Midcrustal Convertersmentioning
confidence: 83%